Role of Subsurface Geo-Energy Pilot and Demonstration Sites in Delivering Net Zero - M. H. Stephenson; D. A. C. Manning; M. J. Spence; L. Stalker; Z. K. Shipton; A. A. Monaghan (Earth Science, Systems and Society)
Recent research suggests that the effects of climate change are already tangible, making the requirement for net zero more pressing than ever. New emissions targets have been announced in April 2021 by various governments, including by the United Kingdom, United States, and China, prior to the Conference of the Parties (COP26) in Glasgow. Part of the solution for net zero will be geo-energy technologies in the subsurface, these include: mine water geothermal, aquifer thermal energy storage (ATES), enhanced geothermal systems and other thermal storage options, compressed air energy storage (CAES), and carbon dioxide capture and storage (CCS) including bioenergy CCS (BECCS). Subsurface net zero technologies have been studied by geologists at laboratory scale and with models, but also require testing at greater-than laboratory scale and in representative conditions not reproducible in laboratories and models. Test, pilot and demonstration facilities aid rock characterisation process understanding and up-scaling, and thereby provide a bridge between laboratory testing and computer modelling and full-scale operation. Examples of test sites that have progressed technology development include the Otway International Test Centre (Australia, CCS) and the Äspö Hard Rock Laboratory (Sweden, geological radioactive waste disposal). These sites have provided scale up for key research questions allowing science issues of relevance to regulation, licencing and permitting to be examined at scale in controlled environments. Successful operations at such sites allow research to be seen at first hand to inform the public, regulators, supply chain companies and investors that such technologies can work safely and economically. A Geological Society conference on the “Role of subsurface research labs in delivering net zero” in February 2021 considered the value of test sites and gaps in their capability. Gaps were identified in two areas: 1) test facilities to aid the design of low cost, high resolution, unobtrusive seismic and other monitoring for a seismically noisy urban environment with a sensitive human population, for example for ATES in urban areas; and 2) a dedicated through-fault zone test site to understand fault transmissivity and reactivation. Conference participants also recommended investment and development in test sites, shared facilities and risk, joint strategies, data interoperability and international collaboration.